2014
DOI: 10.1016/j.midw.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative approaches towards building midwifery capacity in low income countries: A review of experiences

Abstract: the findings provide insights into how collaboration can be established and maintained and how the contribution collaboration makes to capacity building can be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…Across diverse disciplines, capacity building involves intentional, coordinated and mission-driven efforts aimed at strengthening the activities, management and governance of agencies to improve their performance and impact (43, 74). In public health, capacity building can be broad, crossing programmatic (or organizational) silos, or can be specific to a particular topic area such as cancer prevention (137), nutrition (171), maternal and child health (46), HIV prevention (48), or to the professional specializations in performing their tasks identified by certification or licensing requirements (149). …”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
“…Across diverse disciplines, capacity building involves intentional, coordinated and mission-driven efforts aimed at strengthening the activities, management and governance of agencies to improve their performance and impact (43, 74). In public health, capacity building can be broad, crossing programmatic (or organizational) silos, or can be specific to a particular topic area such as cancer prevention (137), nutrition (171), maternal and child health (46), HIV prevention (48), or to the professional specializations in performing their tasks identified by certification or licensing requirements (149). …”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
“…From a primary research perspective, eight articles included some aspects of the experience of expatriate health professional staff (including nurses) whilst working in the described context (Adams et al., ; Asgary & Lawrence, ; Bjerneld, Lindmark, Diskett, & Garrett, ; Busse, Aboneh, & Tefera, ; Chapin & Doocy, ; Chiu, Weng, Chen, Yang, Chiou, & Lee ; Lal & Spence, ; Withers, Browner, & Aghaloo, ), and fourteen described the evaluation of a particular programme whilst serving on a short‐term medical mission trip, which included varying aspects of team dynamics and nursing involvement within those teams (Bido et al., ; Busse et al., ; Chiu, Weng, Chen, Yang, Chiou, et al., ; Chiu, Weng, Chen, Yang, & Lee ; Compton, Lasker, & Rozier, ; Dawson, Brodie, Copeland, Rumsay, & Homer, ; Dawson & Homer, ; Elnawawy, Lee, & Pohl, ; Green, Green, Scandlyn, & Kestler, ; Haglund et al., ; Laleman et al., ; Martiniuk et al., ; Sykes, ; Withers et al., ). There was an overlap of the two categories in three articles (Busse et al., ; Chiu, Weng, Chen, Yang, Chiou, et al., ; Withers et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…An exploration of the effectiveness of an individual surgical programme in Guatemala, from both participant and recipient perspectives, identified a desired collaboration between NGOs and the local health services, but also reported that trust was a vital part in the partnership to strengthen sustainability (Green et al., ). Success should be measured within a commitment to build stable relationship between hosts and those on STMM teams earmarked by genuine sharing of ideas, resources and knowledge and good communication (Dawson et al., ; Elnawawy et al., ). With an identified gap in the literature about how STMMs interact with the communities they serve and the healthcare systems that support them, there is opportunity for greater research into the sustainability of programs delivering short‐term medical care and especially the specific nursing involvement in mentoring and building capacity for ongoing care.…”
Section: Issuesmentioning
confidence: 99%
“…Thirteen authors make a point of emphasising the importance of reciprocity to achieve empowerment. Authors specifically mentioned this at least once under either a special heading [5, 18, 23, 24, 26, 27], or in the introduction [20, 29], the conclusion [21, 22, 25] or abstract [19, 30]. The following quotes illustrate the emphasis that authors put on reciprocity for empowerment.

‘Specifically, the dynamic cooperative atmosphere fosters learning through the sharing of respective experiences….twinning requires the implementation of shared strategies and developmental goals.’ P118 [30]

‘Recognising that the UK has much to learn from low-income countries, the meaning and process of true exchange, reciprocity and mutuality should be further explored.’ P5 [26]

‘ Reciprocity is an important aspect of twinning as the RCM also hopes to strengthen midwifery in the UK.‘ p26 [25]

…”
Section: Resultsmentioning
confidence: 99%